2012
DOI: 10.3109/09638288.2012.717586
|View full text |Cite
|
Sign up to set email alerts
|

Self-efficacy and health status improve after a wellness program in persons with multiple sclerosis

Abstract: A 4-day multidisciplinary educational wellness program can result in improvement in self-efficacy and health-related QOL in persons with MS and can be stable up to at least 6 months. Improvements do not depend on degree of disability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
24
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 30 publications
2
24
0
Order By: Relevance
“…In the U.S.A., Can Do MS, a publically accessible nonprofit wellness program, offers concentrated 4-day interdisciplinary educational wellness programs for PwMS, that promote health seeking behaviors, lifestyle empowerment, and wellness including exercise, and with optional participation of support partners [8]. This educational Can Do MS Program (CDP) has been developed to enable PwMS the uncovering of their existing capabilities [8]. Recently Ng et al observed an improvement in self-efficacy and perceived health after CDP [8].…”
Section: Introductionmentioning
confidence: 99%
“…In the U.S.A., Can Do MS, a publically accessible nonprofit wellness program, offers concentrated 4-day interdisciplinary educational wellness programs for PwMS, that promote health seeking behaviors, lifestyle empowerment, and wellness including exercise, and with optional participation of support partners [8]. This educational Can Do MS Program (CDP) has been developed to enable PwMS the uncovering of their existing capabilities [8]. Recently Ng et al observed an improvement in self-efficacy and perceived health after CDP [8].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Yorkston, Kuehn, Johnson, Ehde, Jensen, & Amtmann (2008) concluded that the subjective importance of participation in everyday situations is relatively independent of measures of mobility, general health, depression, fatigue and pain, but closely linked to self-efficacy. Finally, various intervention studies have been carried out in which self-efficacy is a primary outcome and/or target of treatment (e.g., Ng et al, 2013; Stuifbergen, Becker, Blozis, Timmerman, Kullberg, 2003). For example, Ng et al, (2013) applied a wellness treatment program for a group of individuals with MS and found that it resulted in improved self-efficacy and importantly improved HrQOL.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a study by Hart et al 19 of participants in a wellness program found improvements in depression, functional status, and fatigue. Another study by Ng et al 20 highlighted the positive impact of a wellness program on self-efficacy and health status; again, however, there was no control group. Tesar et al 21 examined the effectiveness of psychological interventions (although not in a formal wellness group), such as cognitive-behavioral strategies and stress-coping training, and found that depressive stress-coping style improved in the experimental group compared with the control group.…”
mentioning
confidence: 99%